2015
DOI: 10.24297/jaa.v5i2.5076
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of some biochemical parameters of apple juices from two cashew varieties as affected by three regions of co´te d Ivoire

Abstract: Some biochemical parameters of juices from two red and yellow cashew apple varieties from three regions of Cote d Ivoire were analyzed. The parameters such as proteins, total soluble solids, total sugars, dry matters, and ashes had contents in juices ranging from 0.35 ± 0.01 % to 0.65 ± 0.02 %, 9.66 ± 0.28 % to 14.40 ± 0.10 %, 270.20 ± 5.15 g/L to 381.04 ± 9.86 g/L, 8.94 ± 0.02 % to 11.45 ± 0.43 % and 1.19 ± 0.01 % to 1.51 ± 0.03 % respectively. Besides, the Analysis of Variance (ANOVA) indicated that the regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 34 publications
1
4
2
Order By: Relevance
“…On the other hand, pressed juice involves the squeezing of the fruit to obtain only the juice that does not contain the skin. Tannins content found in unclarified blended CAJ in this study was relatively higher, compared to those of 1081.99–2561.61 mg/L GAE, reported by Naka et al (2015). Generally, tannin contents found in pressed and blended CAJ, in this study, were higher compared to those of other fruits such as banana (8.38–9.79 mg/100 g) (Kyamuhangire et al, 2006) and apple (8.5 mg/100 g) (Obion et al, 2007).…”
Section: Resultscontrasting
confidence: 74%
See 2 more Smart Citations
“…On the other hand, pressed juice involves the squeezing of the fruit to obtain only the juice that does not contain the skin. Tannins content found in unclarified blended CAJ in this study was relatively higher, compared to those of 1081.99–2561.61 mg/L GAE, reported by Naka et al (2015). Generally, tannin contents found in pressed and blended CAJ, in this study, were higher compared to those of other fruits such as banana (8.38–9.79 mg/100 g) (Kyamuhangire et al, 2006) and apple (8.5 mg/100 g) (Obion et al, 2007).…”
Section: Resultscontrasting
confidence: 74%
“…Results on total sugar for unclarified blended CAJ concur with those of Msoka et al (2017), who reported that total sugar value range from 8875.9 to 21,941.4 mg/100 ml. Similarly, lower total sugar content was found in unclarified blended CAJ when compared to the study done by Marc et al (2012) and Naka et al (2015). In another study, Marc et al (2021) reported low total sugar content (8530 mg/100 ml) for unclarified blended CAJ compared to this study.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…The polyphenol contents are in the range of 1587.59 ± 76.99 to 3043.03 ± 69.87 mg/L of apple juice; these values are lower than those found by some authors which are 2506.510 to 4247.690 [15]. The juice of the yellow variety from the Gbèkè region has the lowest total polyphenol content (1587.59 ± 76.99 mg/L) while that of the red variety from the Zanzan region has the highest total polyphenol content (3043.03 ± 69.87 mg/L) [13].…”
Section: Geographical and Varietal Effectsmentioning
confidence: 60%
“…The results of the study conducted on red and yellow apples in three regions of Côte d'Ivoire showed that, with the exception of the red variety cashew apple juice from the Marahoué region with a refractometric dry extract of 9.66 ± 0.28 ˚Brix, the refractometric dry extract (RDE) values of the apple juices are above 10 ˚Brix which is the minimum value required by the Brazilian legislation [13].…”
Section: Geographical and Varietal Effectsmentioning
confidence: 98%